Elevations in Tumor Necrosis Factor Alpha and Interleukin 6 From Neuronal-Derived Extracellular Vesicles in Repeated Low-Level Blast Exposed Personnel - Edwards, Katie A.; Leete, Jacqueline J.; Smith, Ethan G.; Quick, Alycia; Modica, Claire M.; Wassermann, Eric M.; Polejaeva, Elena; Dell, Kristine C.; LoPresti, Matthew; Walker, Peter; O'Brien, Meghan; Lai, Chen; et al. (Frontiers in Neurology, 2022)
Objective: The purpose of this study was to determine if military service members with histories of hundreds to thousands of low-level blast exposures (i.e., experienced breachers) had different levels of serum and neuronal-derived extracellular vesicle (EV) concentrations of interleukin (IL)-6, IL-10, and tumor necrosis factor alpha (TNFα), compared to matched controls, and if these biomarkers related to neurobehavioral symptoms. Methods: Participants were experienced breachers (n=20) and matched controls without blast exposures (n=14). Neuronal-derived EVs were isolated from serum and identified with mouse anti-human CD171. Serum and neuronal-derived EVs were analyzed for IL-6, IL-10, and TNFα using an ultra-sensitive assay. Results: Serum TNFα concentrations were decreased in breachers when compared to control concentrations (p<0.01). There were no differences in serum concentrations of IL-6, IL-10, or the IL-6/IL-10 ratio between breachers and controls (p’s>0.01). In neuronal-derived EVs, TNFα and IL-6 levels were increased in breachers compared to controls (p’s<0.01), and IL-10 levels were decreased in the breacher group compared to controls (p<0.01). In breachers the IL-6/IL-10 ratio in neuronal-derived EVs was higher compared to controls, which correlated with higher total Rivermead Post-concussion Questionnaire (RPQ) scores (p’s<.05). Conclusions: These findings suggest that exposure of personnel to high numbers of low-level blast over a career may result in enduring central inflammation that is associated with chronic neurological symptoms. The data also suggest that peripheral markers of inflammation are not necessarily adequate surrogates for central neuroinflammation.